Protein misfolding cyclic amplification induces the conversion of recombinant prion protein to PrP oligomers causing neuronal apoptosis. (13th April 2015) - Yuan, Zhen; Yang, Lifeng; Chen, Baian; Zhu, Ting; Hassan, Mohammad Farooque; Yin, Xiaomin; Zhou, Xiangmei; Zhao, Deming
Abstract: The formation of neurotoxic prion protein (PrP) oligomers is thought to be a key step in the development of prion diseases. Recently, it was determined that the sonication and shaking of recombinant PrP can convert PrP monomers into β‐state oligomers. Herein, we demonstrate that β‐state oligomeric PrP can be generated through protein misfolding cyclic amplification from recombinant full‐length hamster, human, rabbit, and mutated rabbit PrP, and that these oligomers can be used for subsequent research into the mechanisms of PrP‐induced neurotoxicity. We have characterized protein misfolding cyclic amplification‐induced monomer‐to‐oligomer conversion of PrP from three species using western blotting, circular dichroism, size‐exclusion chromatography, and resistance to proteinase K (PK) digestion. We have further shown that all of the resulting β‐oligomers are toxic to primary mouse cortical neurons independent of the presence of PrP C in the neurons, whereas the corresponding monomeric PrP were not toxic. In addition, we found that this toxicity is the result of oligomer‐induced apoptosis via regulation of Bcl‐2, Bax, and caspase‐3 in both wild‐type and PrP −/− cortical neurons. It is our hope that these results may contribute to our understanding of prion transformation within the brain. We found that β‐state oligomeric PrPs can be generated through protein misfolding cyclic amplification (PMCA) from recombinant full‐length hamster, human, rabbit, and mutated rabbit PrP. β‐oligomers are toxic to primary mouse cortical neurons independent of the presence of PrP C in the neurons, while the corresponding monomeric PrPs were not toxic. This toxicity is the result of oligomers‐induced apoptosis via regulation of Bcl‐2, Bax, and caspase‐3. These results may contribute to our understanding of prion transformation within the brain. Abstract : We found that β‐state oligomeric PrPs can be generated through protein misfolding cyclic amplification (PMCA) from recombinant full‐length hamster, human, rabbit, and mutated rabbit PrP. β‐oligomers are toxic to primary mouse cortical neurons independent of the presence of PrP C in the neurons, while the corresponding monomeric PrPs were not toxic. This toxicity is the result of oligomers‐induced apoptosis via regulation of Bcl‐2, Bax, and caspase‐3. These results may contribute to our understanding of prion transformation within the brain.